Saving the World's Deciduous Forests: Ecological Perspectives from East Asia, North America, and Europe - Robert A. Askins (Yale University Press, 2014)
My original plan was to write a book focusing on conservation of wildlife in the deciduous forests of East Asia, eastern North America, and Eu rope. Animals can be saved only if the plants that sustain them are protected, however, and all of these organisms depend on functioning forest ecosystems. The scope of the book therefore expanded beyond a discussion of populations of par tic u lar species of mammals, birds, and other animals to encompass the history and ecol ogy of entire forest ecosystems. Effective wildlife conservation must be grounded in this broader perspective. Comparison of deciduous forests of East Asia, eastern North America, and Eu rope is especially intriguing because these ecosystems have a common origin but have evolved in isolation for millions of years. Do these forest ecosystems function in similar ways because of their common origin and similar climates? Or have they evolved in distinctly different ways because of their long separation? If ecological pro cesses are basically similar on the three continents, then ecological insights and conservation strategies learned on one continent can be applied effectively to the other two. Other books have already cata logued and described the different types of deciduous forests on each continent, so I did not go into detail about variation in deciduous forests within continents. Instead, my goal was to compare the ecol ogy of deciduous forests on different continents. Ultimately I was searching for general ecological patterns and for widely applicable solutions to conservation problems. Although deciduous forests are similar on the three continents, they have distinctly different geological, biological, and cultural histories. A historical perspective at a wide range of time scales is important for understanding the similarities and differences among continents. I therefore discuss the history of these forests in both deep time (at scales of millions of years to tens of thousands of years) and in recent time (at time scales spanning those used by archaeologists, historians, and fi eld ecologists). I emphasize environmental threats that have a global impact on the biological diversity of deciduous forests, such as high densities of deer, forest fragmentation, tree pathogens, and climate change. There are other environmental problems (such as acid deposition, air pollution, unsustainable hunting, and pesticide contamination) that I have not emphasized because their effects tend to be more localized and less pervasive in deciduous forests around the world.